2022
DOI: 10.1128/spectrum.02797-22
|View full text |Cite
|
Sign up to set email alerts
|

σ P -NagA-L1/L2 Regulatory Circuit Involved in ΔompA 299-356 -Mediated Increase in β-Lactam Susceptibility in Stenotrophomonas maltophilia

Abstract: Porins of Gram-negative bacteria generally act as channels that allow the entry or extrusion of molecules. Moreover, the structural role of porins in stabilizing the outer membrane by interacting with peptidoglycan (PG) and the outer membrane has been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Recently, we reported that ompA is highly expressed in logarithmic-phase S. maltophilia KJ cells ( 38 ). We characterized an in-frame deletion ompA mutant of S. maltophilia KJ, originally termed KJΔOmpA ( 39 ) and later renamed KJΔOmpA 299–356 ( 40 ). We also reported that the truncated OmpA protein can be stably embedded in the outer membrane but loses contact with peptidoglycan (PG) ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we reported that ompA is highly expressed in logarithmic-phase S. maltophilia KJ cells ( 38 ). We characterized an in-frame deletion ompA mutant of S. maltophilia KJ, originally termed KJΔOmpA ( 39 ) and later renamed KJΔOmpA 299–356 ( 40 ). We also reported that the truncated OmpA protein can be stably embedded in the outer membrane but loses contact with peptidoglycan (PG) ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…We characterized an in-frame deletion ompA mutant of S. maltophilia KJ, originally termed KJΔOmpA ( 39 ) and later renamed KJΔOmpA 299–356 ( 40 ). We also reported that the truncated OmpA protein can be stably embedded in the outer membrane but loses contact with peptidoglycan (PG) ( 40 ). KJΔOmpA 299–356 exhibits decreased conjugation ability and swimming motility ( 39 ), as well as increased susceptibility to β-lactams ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations